Identification of Genetic Loci Affecting Flag Leaf Chlorophyll in Wheat Grown under Different Water Regimes - Yang, Bin; Wen, Xiaojie; Wen, Hongwei; Feng, Yanru; Zhao, Jiajia; Wu, Bangbang; Zheng, Xingwei; Yang, Chenkang; Yang, Sanwei; Qiao, Ling; Zheng, Jun (Frontiers in Genetics, 2022)
Chlorophyll content of flag leaf is an important trait to reflect the drought resistance of wheat under drought stress. Understanding the genetic mechanism of regulating flag leaf chlorophyll can accelerate the breeding of drought resistant wheat varieties. In this study, we constructed a recombinant inbred line (RIL) population with high chlorophyll content in drought-senstive variety DH118 and drought-resistant variety Jinmai 919, and analyzed the chlorophyll content of flag leaves in 6 experimental conditions under well-watered and drought stress by QTL analysis. A total of 42 additive QTLs controlling flag leaf chlorophyll were detected, and the contribution rate to phenotype was 4.67% to 23.25%. Among them, 12 additive QTLs were detected under well-watered conditions and 18 additive QTLs were detected under drought stress. Most of the QTLs detected under two kinds of water conditions were different. Four major QTLs (Qchl.saw-3B.2, Qchl.saw-5A.2, Qchl.saw-5A.3 and Qchl.saw-5B.2) were detected under different environments. Among them, Qchl.saw-3B.2 was not only proved to be stably expressed without the influence of genetic background, but also detected under several well-watered conditions, which may be more suitable for molecular marker-assisted breeding of watery land varieties. In addition, Qchl.saw-5A.3 is a new stable expression QTL, which could be detected in all drought stress environments, and could explain up to 23.25% of the phenotypic variation, so it has the potential to be used in drought-resistant molecular marker-assisted breeding.